The Love Scam. Erotic Scams carried out by Women in Costa Rica between 1970 and 1990 published in the Newspaper La República - Sequeira Rovira, Paula (2025)
This paper analyzes a crime that appeared in Costa Rica between the 1970s and early 1990s. It was called “the love scam” and consisted of erotic scams, in which the victims were men who were deceived before, during, or after having a casual sexual encounter. The purpose is to rescue this story to provoke a reflection on the distinguishing features of “men” and “women” of that time and to show that there was a certain ambiguity in the expected gender roles within the reviewed news. The research is carried out based on the review of the events section of the newspaper La República during the cited decades. In the conclusion, it is analyzed how the ideas that were repeated about these crimes (lustful but naive men versus astute women not interested in traditional sexual morality) suggested the dangerousness of any woman who was interested in casual sex patterns.